THE ROLE OF SOCIAL FORESTRY PROGRAM IN CONFLICT RESOLUTION IN FOREST AREAS IN AGAM DISTRICT - Syafarman, Syafarman; Frinaldi, Aldri; Rembrandt, Rembrandt (Fakultan Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura, 2025)
West Sumatra Province has an area of approximately 4,229,730 hectares, with approximately 54.43% or approximately 2,300,000 hectares being state forest areas. This forest area consists of conservation forests, protected forests, and production forests. The authority of the West Sumatra Provincial Government based on regional autonomy is to manage protected forest areas and production forests, namely with an area of 2.3 million hectares. Based on data from the West Sumatra Provincial Forestry Service in 2023, the area of forest areas managed through the social forestry program reached 50,410 hectares. The management area of KPHL Agam Raya is 39,285 hectares with a social forestry permit area of 16,247 hectares. To enforce environmental law and resolve conflicts by communities around the forest, with the presence of a social forestry program that provides space for communities around the forest for communities who have already or are trying in protected forest areas and production forests so as not to violate the law, the community can properly manage the area legally which is given management rights by the government through the Ministry of Environment and Forestry to utilize the potential of the forest without having to reduce the protection and conservation functions. The role of social forestry in the context of conflict resolution and environmental law enforcement in the forestry sector is as follows: Prevention of Land Conflicts and Forest Damage: Government programs in the form of social forestry programs can provide legal certainty for communities in managing forests through schemes such as Village Forests, Community Forests, People's Plantation Forests, Forestry Partnerships, and Customary Forests. With this legal certainty, land conflicts between communities and other parties, including companies, can be minimized. In addition, communities who have the legal right to manage forests tend to be more committed to maintaining the sustainability of forest areas rather than encroaching, burning or illegal logging that can damage the area. In West Sumatra, there are several examples of the success of the Social Forestry program in resolving conflicts. For example, in the Agam and South Solok areas, community-based forest management has succeeded in reducing tenure conflicts and improving local welfare. In some cases, recognition of customary forests has also helped reduce conflicts with large companies. Social Forestry in West Sumatra has made a positive contribution to resolving conflicts, but it needs ongoing support from various parties to ensure its long-term impact.